2016
DOI: 10.1111/ced.12933
|View full text |Cite
|
Sign up to set email alerts
|

Oral clindamycin and rifampicin combination therapy for hidradenitis suppurativa: a prospective study and 1-year follow-up

Abstract: Oral clindamycin with oral rifampicin for 12 weeks is an effective and tolerable regimen for HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 20 publications
1
39
2
3
Order By: Relevance
“…In this combination, clindamycin is added to overcome the antibiotic resistance against rifampicin, and the dose of clindamycin reaches subtherapeutic levels after 2 weeks of therapy because of cytochrome p450 induction by rifampicin (Albrecht, Baine, Ladizinski, Jemec, & Bigby, 2018). Efficacy of this combination was reported in a few case series and case studies (Dessinioti, Zisimou, Tzanetakou, Stratigos, & Antoniou, 2016;Gener et al, 2009;van der Zee, Boer, Prens, & Jemec, 2009). In one of these reports, patients had a significant reduction in the baseline Sartorius score (Gener et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this combination, clindamycin is added to overcome the antibiotic resistance against rifampicin, and the dose of clindamycin reaches subtherapeutic levels after 2 weeks of therapy because of cytochrome p450 induction by rifampicin (Albrecht, Baine, Ladizinski, Jemec, & Bigby, 2018). Efficacy of this combination was reported in a few case series and case studies (Dessinioti, Zisimou, Tzanetakou, Stratigos, & Antoniou, 2016;Gener et al, 2009;van der Zee, Boer, Prens, & Jemec, 2009). In one of these reports, patients had a significant reduction in the baseline Sartorius score (Gener et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to flare, the terms recurrence and relapse were used more frequently in the literature and had a higher proportion of studies with a definition (Table S1; see Supporting Information). [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Again, in contrast to flare, recurrence or relapse were more frequently associated with an increase in HS activity after a surgical intervention. Of the 19 studies that defined either relapse or recurrence, six (32%, six of 19) used the term in association with a medical intervention, while the majority (68%, 13 of 19) used the terms for a surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…given in combination with rifampicin [600 mg daily given as either 1 or 2 doses] for 10 weeks) has proved beneficial, with variable results 8387. In a study conducted by van der Zee et al, 47% of HS patients receiving systemic clindamycin/rifampicin treatment reported total remission after 10 weeks, while an additional 35% of subjects experienced at least some improvement, whereas another survey reported that 70/116 patients (~70%) had significant improvement after 10 weeks of treatment 83,85.…”
Section: Treatmentmentioning
confidence: 99%